Obstetrical Healthcare Personnel's Attitudes and Perceptions on Maternal Vaccination with Tetanus-Diphtheria-Acellular Pertussis and Influenza. (22nd April 2013) - Vijayan, Vini; Kim, Matthew; Zangwill, Kenneth M.; Mink, Chrisanna; Yeh, Sylvia
Abstract : Objectives . To assess perceptions of obstetrical healthcare personnel (HCP) regarding routine delivery of Tdap and influenza vaccines to pregnant and postpartum women and identify perceived barriers to vaccination. Methods . Anonymous Web-based survey of obstetricians and nurses caring for pregnant and/or postpartum women. Results . We contacted 342 HCP and received 163 (48%) completed surveys (33/142 (23%) obstetricians, 130/200 (65%) nurses). Among obstetricians, 72% and 63% thought it was "beneficial" to immunize postpartum women against influenza and pertussis, respectively. Only 8% reported vaccinating >75% of pregnant women in their care against influenza. Similarly, <1% of obstetricians reported vaccinating against pertussis. Of all HCP surveyed, 92% and 58% were familiar with ACIP recommendations for influenza and pertussis, respectively. Reported perceived barriers included patient refusal to be vaccinated, reimbursement difficulties, and discomfort in providing vaccine education. Ninety-four percent of respondents agreed that standing orders would be helpful to ensure postpartum vaccination. Conclusions . HCP were less familiar with ACIP recommendations for Tdap compared to influenza vaccines. Substantial discrepancy existed between perceived benefit of vaccination and reported immunization practices. Most identified barriers could be addressed with provider training; however, other barriers require review and changes in systematic policies related to vaccine reimbursement.